A review of the literature on sexual assault perpetrator characteristics and behaviors - Greathouse, Sarah Michal (Research report (Rand Corporation), 2015)
"Sexual assault continues to be a pervasive problem, both for society in general and within the military community. To assist the Air Force in its continued efforts to combat sexual assault within its ranks, we reviewed the existing empirical literature on the characteristics and behaviors of adult perpetrators who commit sexual assault against other adults. Our search was not limited to studies of military populations. While a vast majority of the existing literature has focused on sole male perpetrators who assault female victims, we identified some research on other types of perpetrators, including female sexual assault perpetrators, men who perpetrate assault against other men, and perpetrators who participate in group sexual assault. This body of research indicates that adult perpetrators are diverse in terms of their demographics, background characteristics, and motivations. Moreover, research indicates that sexual assault perpetration is likely influenced by a combination of factors, including an individual's developmental and family history; his or her personality, including attitudes/cognitions; and environmental factors, including peer attitudes and alcohol consumption. The complexity of factors that influence sexual assault perpetration and the multiple pathways that lead to an attack make it difficult to predict whether an individual is prone to commit sexual assault. While predicting sexual assault perpetration is problematic, we identified a number of factors related to perpetration that may be relevant for intervention efforts and offer recommendations for the Air Force"--Publisher's web site